Combinatorial antimicrobial efficacy and mechanism of linalool against clinically-relevant Klebsiella pneumoniae - Yang, Shun Kai; Yusoff, Khatijah; Ajat, Mokrish; Wee, Chien Yeong; Yap, Polly Soo-Xi; Lim, Swee Hua Erin; Lai, Kok Song (Frontiers Media, 2021)
Antibiotic-adjuvant combinatory therapy serves as a viable treatment option in addressing antibiotic resistance in the clinical setting. This study was carried out to assess and characterize the adjuvant potential and mode of action of linalool against carbapenemase-producing Klebsiella pneumoniae (KPC-KP). Linalool exhibited bactericidal activity alone (11,250 μg/ml) and in combination with meropenem (5,625 μg/ml). Comparative proteomic analysis showed significant reduction in the number of cytoplasmic and membrane proteins, indicating membrane damage in linalool-treated KPC-KP cells. Upregulation of oxidative stress regulator proteins and downregulation of oxidative stress-sensitive proteins indicated oxidative stress. Zeta potential measurement and outer membrane permeability assay revealed that linalool increases the bacterial surface charge as well as the membrane permeability. Intracellular leakage of nucleic acid and proteins was detected upon linalool treatment. Scanning and transmission electron microscopies further revealed the breakage of bacterial membrane and loss of intracellular materials. Linalool induced oxidative stress by generating reactive oxygen species (ROS) which initiates lipid peroxidation, leading to damage of the bacterial membrane. This leads to intracellular leakage, eventually killing the KPC-KP cells. Our study demonstrated that linalool possesses great potential in future clinical applications as an adjuvant along with existing antibiotics attributed to their ability in disrupting the bacterial membrane by inducing oxidative stress. This facilitates the uptake of antibiotics into the bacterial cells, enhancing bacterial killing.